2002
DOI: 10.1177/082585970201800405
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Professional Short-Term Group Intervention for Informal Caregivers of Patients Using a Home Palliative Care Service

Abstract: Informal carers of home palliative care patients have high unmet needs. However, interventions for carers are few. This research-based short-term group intervention addresses the information and support needs of carers. Multiprofessional informal teaching is combined with peer support. The intervention was designed by integrating the findings from a qualitative study and the evidence on needs and interventions, in order to address the key issues of feasibility, acceptability, and accessibility. Qualitative dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1
12

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 25 publications
4
16
1
12
Order By: Relevance
“…Five studies were pre-test/post-test designs without comparison groups and all were graded weaker in evidence [31-35]. Finally, two studies were examined via qualitative methods (vis semi-structured interviews) and were therefore graded as weak evidence [36,37]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies were pre-test/post-test designs without comparison groups and all were graded weaker in evidence [31-35]. Finally, two studies were examined via qualitative methods (vis semi-structured interviews) and were therefore graded as weak evidence [36,37]. …”
Section: Resultsmentioning
confidence: 99%
“…However, Harding et al [30] reported that a short-term intervention promoting self-care had no significant benefit to carers' psychosocial health or well-being. However a qualitative study with family carers who participated in the intervention revealed that valued outcomes were validation of feelings, identification with other carers, opportunities for questions and provision of support to others [36]. …”
Section: Resultsmentioning
confidence: 99%
“…As in previous research, carers and nursing staff reported uncertainty and information needs in areas such as physical care, patient comfort, hygiene assistance, equipment, symptom management and managing diet [1,2,5]. Following Hudson’s application of a transactional coping model and proposed coping resources in care-giving situations, these skill and knowledge areas could be conceptualised as competence factors [11].…”
Section: Discussionmentioning
confidence: 98%
“…Henriksson and Andershed (2007) found that a support group program provided a sense of safety and relief in the everyday lives of participants. Harding et al (2002) found that identifying with others and validating feelings, asking questions of professionals, and providing mutual support were valuable group outcomes and Milberg et al (2005) concluded that support groups for family members seemed to make a valuable contribution during ongoing palliative care. Harding et al (2002) found that identifying with others and validating feelings, asking questions of professionals, and providing mutual support were valuable group outcomes and Milberg et al (2005) concluded that support groups for family members seemed to make a valuable contribution during ongoing palliative care.…”
Section: Introductionmentioning
confidence: 99%